Prediction of Weld Bead Geometry for Small-Wire Submerged Arc Welding in 1G position / Ghalib Tham...[et al.] - Tham, Ghalib; Mohamad Nor, Nur Hafiez; Faruqi, Mohamad; Saedon, Juri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Small-wire Submerged Arc Welding (SAW) is a low-cost alternative to the conventional SAW. In robotic or mechanized welding system, the welding bead geometry and welding parameter have to be known before welding. Developing them by trial and error is costly and wasteful practice in the long run. Therefore, there is a need to develop a tool to predict the correct bead geometry. A robotic small-wire SAW was employed to deposit bead-on-plate on carbon steel in 1G position, using a range of welding parameter permitted by the power source. Quality welded samples were cut at cross-section, polished and etched to display their macrostructure. The bead geometry was measured; the correlation between bead geometry and heat input was plotted. Without considering the bead penetration, the measured values of bead geometry are found to be quite scattered about the trend line, except the bead width. By applying the trend-line equations in prediction of bead geometry, only the bead width can be predicted accurately, where the deviation between predicted bead width and measured bead width is consistently less than 1mm. By grouping the measured bead geometry data based on 5 levels of bead penetration, when plotting the bead geometry with respect to heat input, all the bead geometry data aligned closely along their respective trend-lines, thus all elements of bead geometry can be predicted with high accuracy. The deviation of all elements of bead geometry and the values of mean average deviation (MAD) is less than 1mm.